2020
DOI: 10.1002/jbio.201960163
|View full text |Cite
|
Sign up to set email alerts
|

Organelle specific simultaneous Raman/green fluorescence protein microspectroscopy for living cell physicochemical studies

Abstract: We demonstrate a novel bio-spectroscopic technique, "simultaneous Raman/GFP microspectroscopy". It enables organelle specific Raman microspectroscopy of living cells. Fission yeast, Schizosaccharomyces pombe, whose mitochondria are green fluorescence protein (GFP) labeled, is used as a test model system. Raman excitation laser and GFP excitation light irradiate the sample yeast cells simultaneously. GFP signal is monitored in the anti-Stokes region where interference from Raman scattering is negligibly small. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Various methods for the analysis of the 2D data have been proposed for chemometrics. Among them, the multivariate curve resolution alternate least square (MCR-ALS) analysis was employed to retrieve the spectral ( V l ′) and temporal ( U l ′) components from the 2D data for comparison with the SVD and reconstruction method . The spatial distribution of several compounds exhibiting a unique spectral pattern is taken from the Raman mapping image using the MCR-ALS method . The Frobenius norm ∥ M – U l ′ V l ′∥ 2 and the L1 norms of U l ′ and V l ′ multiplied by 10 –5 were minimized by the least square method under the non-negativity constraint for U l ′ and V l ′.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods for the analysis of the 2D data have been proposed for chemometrics. Among them, the multivariate curve resolution alternate least square (MCR-ALS) analysis was employed to retrieve the spectral ( V l ′) and temporal ( U l ′) components from the 2D data for comparison with the SVD and reconstruction method . The spatial distribution of several compounds exhibiting a unique spectral pattern is taken from the Raman mapping image using the MCR-ALS method . The Frobenius norm ∥ M – U l ′ V l ′∥ 2 and the L1 norms of U l ′ and V l ′ multiplied by 10 –5 were minimized by the least square method under the non-negativity constraint for U l ′ and V l ′.…”
Section: Discussionmentioning
confidence: 99%
“…36 The spatial distribution of several compounds exhibiting a unique spectral pattern is taken from the Raman mapping image using the MCR-ALS method. 38 The Frobenius norm ∥M−U l ′V l ′∥ 2 and the L1 norms of U l ′ and V l ′ multiplied by 10 −5 were minimized by the least square method under the non-negativity constraint for U l ′ and V l ′. Figure 6a,b shows the deduced spectral and temporal vectors of the three positional isomers.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Multivariate curve resolution-ALS was performed using the IGOR Pro (WaveMatrics, Inc., Oregon, USA). More than 300 spectra from three datasets of enrofloxacin in water, spiked pig urine, and urine samples were analyzed using MCR-ALS to verify the concentration of antibiotics [ 24 ]. Standard antibiotics Raman spectra were used as references for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by Li et al [161], this approach could be used to evaluate the functionalities of lipid droplets and bacteria by analyzing the finger print region showing the relative abundance of chemical functions, as reported in Figure 6. This approach was also used to monitor the organelle in vivo [162,163], the chromosomes [164], and for the evaluation of the hemoglobin in red blood cells and for the density of water inside the cells [165]. This last study is particularly interesting because it proved the presence of a strong and highly organized hydrogen bond network in the cytosol.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Nasdala et al [169] reported that this technique can investigate inside the inner structure of mineralogic samples in different temperature and pressure conditions. These in This approach was also used to monitor the organelle in vivo [162,163], the chromosomes [164], and for the evaluation of the hemoglobin in red blood cells and for the density of water inside the cells [165]. This last study is particularly interesting because it proved the presence of a strong and highly organized hydrogen bond network in the cytosol.…”
Section: Mineralogymentioning
confidence: 99%